Development Stages of the Couplet of (Bulūgh al-Amal fī Tafsīl al-Jumal) through Two Editions of the Book: Discourse Analysis - AlMuqaimi, Majid Hamood Subait; Pa, Mat Taib; Rifa’in@Mohd Rifain, Syakirah (Al-Ḍād Journal, 2023)
The research aims to study the stages of development of the couplet of (Bulūgh al-Amal fī Tafsīl al-Jumal) in the two editions of the book, where the first edition was the beginning, but Imam Al-Salmi modified and increased it in the second edition, then increased and modified after the second edition, which demonstrates that the science grows over time. The Imam also left the amendments to show that the science is gaining its ground and that the beginning is not like the end and in the end the research aims at shedding light on the differences between these versions. The sentences as well as the modifications made by Imam Al-Salmi on the first version, then the amendments he made before the second version, and then the amendments he made to the second version, that show the importance of language for Imam Al-Salmi. It became clear from this research the following results: 1- The humility of Imam Al-Salmi, as he left the original and the amendment to show the shortcomings in his original system, 2- The amendments made by Imam Al-Salmi increased the strength and integrity of the system, 3- Imam Al-Salmi’s keenness in the amendments to facilitate the matter in the student to make it easier for him to express. The research necessitates prospective work on studying the versions and showing the differences between them, which applies the language and reveals more of its secrets and shows the reasons for the difference, which facilitates the understanding of the couplet and its parsing for students of Arabic language grammar. Keywords: Stages of development, couplet, Bulūgh al-Amal, Tafsīl al-Jumal, Imam Al-Salmi